Induction of the NEK family of kinases in the lungs of mice subjected to cecal ligation and puncture model of sepsis. Issue 4 (2nd October 2021) - Uddin, Mohammad A.; Akhter, Mohammad S.; Kubra, Khadeja-Tul; Barabutis, Nektarios
ABSTRACT: Endothelial barrier dysfunction (EBD) is the hallmark of Acute Respiratory Distress Syndrome (ARDS), a potentially lethal respiratory disorder associated with the COVID-19 – related deaths. Herein, we employed a cecal ligation and puncture (CLP) murine model of sepsis, to evaluate the effects of sepsis-induced EBD in the expression of the never in mitosis A (NIMA)-related kinases (NEKs). Members of that family of kinases regulate the activity and expression of the tumor suppressor P53, previously shown to modulate the actin cytoskeleton remodeling. Our results introduce the induction of NEK2, NEK3, NEK4, NEK7, and NEK9 in a CLP model of sepsis. Hence, we suggest that NEKs are involved in inflammatory processes and are holding the potential to serve as novel therapeutic targets for pathologies related to EBD, including ARDS and sepsis. Further studies will delineate the underlying molecular events and their interrelations with P53.